Treatment of Infertility in Men with Post-traumatic Stress Disorder (PTSD) with the Method of Intrauterine Insemination - Elezaj, Shkelzen (Med Arch, 2015)
OBJECTIVE: Our objective was to determine the effect of PTSD on changing the quality of sperm in veterans with PTSD, and the percentage of successful procedures intrauterine insemination (IUI) as a first-line treatment of male infertility patients with post-traumatic stress disorder (PTSD). PATIENTS AND METHODS: The study is designed as a prospective observational study. The study was started from February 2013 until May of 2014. Our study included a total of 51 patients who were treatment for infertility in private Hospital for gynecology, endocrinology and infertility, IVF Center in Peja, and those who were outpatients treated for chronic PTSD in the Polyclinic, Biolab-Zafi, in Klina the Republic of Kosovo. All subjects divide into two groups; The first, consisting of 21 respondents to the participants of the war in Kosovo, which was established diagnosis of PTSD. The second group of 30 who have not lived in Kosovo for the time War, and without signs of PTSD. RESULTS: Subjects with PTSD were somewhat older than the control group (p = 0.235) but it was not a significant difference (44.5 ± 5.6 vs 43.8 ± 2.3). When the question of type of infertility, secondary infertility is significantly higher in patients with PTSD (62% vs 20%) (Table 2). The total number of sperm and semen volume no significant differences between the two groups (p > 0.05). Sperm motility showed a significant reduction in cases of PTSD (p <0.0001), from observation semen parameters were found more abnormal forms of spermatozoa in the ejaculate cases with PTSD (p < 0.0001) (Table 2). The percentage of pregnancies IUI procedure was slightly higher in patients with PTSD than the control group without PTSD (19% vs. 16.6%). CONCLUSION: A combination of analytical oriented psychotherapy techniques and assisted reproductive techniques (ART) such as IUI procedures, increases the chances for healing infertility in patients with PTSD.